IBU DAN IKLAN TELEVISI (TINJAUAN TERHADAP IKLAN PRODUK UNTUK BALITA DI TELEVISI) - Intan Kemala; Titi Antin (Marwah: Jurnal Perempuan, Agama dan Jender, 2011)
Advertisement is an easy media to persuades the society, but sometime advertisement inculcate ideology which is contrast with social reality, so that peep out sham reality. Producer, copywriter and visualizer, of media have to think the good side and impact to emerge from the advertisement for the shake of future nation. Mother has to have filter in pulling back the displaying of advertisement which appeal and mislead, with selective assessing, choosing, then decide product to be used for her household. This will not realize without support the knowledge of family ( in this case, father as the head of household ). It is not easy to fight against the persuation of television advertisement because there is a desire to buy although the products which will bought not yet become a need.